Real world experience of patients with amyotrophic lateral sclerosis (ALS) in the treatment of spasticity using tetrahydrocannabinol:cannabidiol (THC:CBD) - Meyer, Thomas (BMC Neurol, 2019)
BACKGROUND: Treatment of spasticity poses a major challenge in amyotrophic lateral sclerosis (ALS) patient management. Delta-9-tetrahydrocannabinol (THC):cannabidiol (CBD) oromucosal spray (THC:CBD), approved for the treatment of spasticity in multiple sclerosis, serves as a complementary off-label treatment option in ALS-related spasticity. However, few structured data are available on THC:CBD in the treatment of spasticity in ALS. METHOD: A retrospective mono-centric cohort study was realised in 32 patients that meet the following criteria: 1) diagnosis of ALS, 2) ALS-related spasticity; 3) treatment with THC:CBD. Spasticity was rated using the Numeric Rating Scale (NRS). Patient’s experience with THC:CBD was assessed using the net promoter score (NPS) and treatment satisfaction questionnaire for medication (TSMQ-9) as captured through telephone survey or online assessment. RESULTS: The mean dose THC:CBD were 5.5 daily actuations (range < 1 to 20). Three subgroups of patients were identified: 1) high-dose daily use (≥ 7 daily actuations, 34%, n = 11), 2) low-dose daily use (< 7 daily actuations, 50%, n = 16), 3) infrequent use (< 1 daily actuation, 16%, n = 5). Overall NPS was + 4.9 (values above 0 express a positive recommendation to fellow patients). Remarkably, patients with moderate to severe spasticity (NRS ≥ 4) reported a high recommendation rate (NPS: + 29) in contrast to patients with mild spasticity (NRS < 4; NPS: − 44). For the three main domains of TSQM-9 high mean satisfaction levels were found (maximum value 100): effectiveness 70.5 (±22.3), convenience 76.6 (±23.3) and global satisfaction 75.0 (±24.7). CONCLUSION: THC:CBD is used in a wide dose range suggesting that the drug was applied on the basis of individual patients’ needs and preferences. Contributing to this notion, moderate to severe spasticity was associated with an elevated number of daily THC:CBD actuations and stronger recommendation rate (NPS) as compared to patients with mild spasticity. Overall, treatment satisfaction (TSQM-9) was high. The results suggest that THC:CBD may serve as a valuable addition in the spectrum of symptomatic therapy in ALS. However, prospective studies and head-to-head comparisons to other spasticity medications are of interest to further explore the effectiveness of THC:CBD in the management of spasticity, and other ALS-related symptoms. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12883-019-1443-y) contains supplementary material, which is available to authorized users.